Implementation of Moral Education Through the Karang Taruna Organization of Kaliputih Hamlet Sumbersuko Gempol - Nurul Fitriani; Ahmad Marzuki; Ali Mohtarom (Sean Institute, 2023)
Moral education is the process of educating, nurturing, shaping, and offering both official and informal training regarding morality and intelligent thinking. The goal of moral education is to ensure that people are always on the right path, which is the path that Allah SWT has predetermined, and that they are in the truth. In order to determine the motivating and impeding factors in the Implementation of Moral Education Through the Youth Organization of Dusun Kaliputih Sumbersuko Gempol, the purpose of this study is to analyze moral education's implementation in greater detail. Whereas the application of moral education is included in the theoretical analysis in this work. The findings of this study suggest that moral education can help the Dusun Kaliputih people develop good morals, politeness in speech, noble behavior, wisdom, civility, sincerity, and honesty. There are variables that assist moral education there, such as: Motivating the Community, Environmental Factors, Facilities, and Religious Leaders are the first three categories. Other adapum inhibitors of atra: 1) A lack of young knowledge of moral education; 2) a lack of youth time, which is one of the issues impeding the implementation of moral education; and 3) a lack of parental and environmental motivation.